2017
DOI: 10.1016/s2214-109x(17)30246-2
|View full text |Cite
|
Sign up to set email alerts
|

Progress and priorities for reproductive, maternal, newborn, and child health in Kenya: a Countdown to 2015 country case study

Abstract: SummaryBackgroundProgress in reproductive, maternal, newborn, and child health (RMNCH) in Kenya has been inconsistent over the past two decades, despite the global push to foster accountability, reduce child mortality, and improve maternal health in an equitable manner. Although several cross-sectional assessments have been done, a systematic analysis of RMNCH in Kenya was needed to better understand the push and pull factors that govern intervention coverage and influence mortality trends. As such, we aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
111
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 22 publications
1
111
0
Order By: Relevance
“…Kenya has a young population with an estimated 10.5 million adolescents aged 10-19 years, corresponding to 22.5% of the country's total population [12]. The maternal mortality ratio has been declining during the last decade to reach 510 in 2015 [13]. Since 2010, a revised abortion law in Kenya allow abortion when the life or health of a woman is in danger [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kenya has a young population with an estimated 10.5 million adolescents aged 10-19 years, corresponding to 22.5% of the country's total population [12]. The maternal mortality ratio has been declining during the last decade to reach 510 in 2015 [13]. Since 2010, a revised abortion law in Kenya allow abortion when the life or health of a woman is in danger [14].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2010, a revised abortion law in Kenya allow abortion when the life or health of a woman is in danger [14]. Still, unsafe abortion remains the leading cause of maternal deaths in adolescent girls [13]. The contraceptive prevalence rate has increased steadily to 61.6 among married women aged 15-49 years in 2016 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have cited the importance of a mother's care and Nduati et al (14) reported higher mortality and morbidity rates among children whose mothers had died. Therefore, it is common knowledge that maternal health is an important determinant of infant health (16,26). Since our work focuses on infant survival and wellbeing, it is inevitable to consider the aspect of maternal health as the two are interlinked.…”
Section: Introductionmentioning
confidence: 99%
“…The 2015 countdown analysis, replaced by the countdown 2030, annually monitors the progress in the coverage indicators of the countdown countries at the national level [6,8,16]. Though there has been substantial progress achieved by many countries, the achievement was uneven and need more significant acceleration [6,[17][18][19][20][21]. Concerns about health inequity indicate that there is a need for analysis of health indicators at the microgeographic level or the population subgroups.…”
Section: Introductionmentioning
confidence: 99%